Mitochondrial Dysfunction, Oxidative Stress, and Therapeutic Strategies in Diabetes, Obesity, and Cardiovascular Disease - Karina-Alexandra Cojocaru; Ionut Luchian; Ancuta Goriuc; Lucian-Mihai Antoci; Cristian-Gabriel Ciobanu; Roxana Popescu; Cristiana-Elena Vlad; Mihaela Blaj; Liliana Georgeta Foia (MDPI AG, 2023)
Mitochondria are subcellular organelles involved in essential cellular functions, including cytosolic calcium regulation, cell apoptosis, and reactive oxygen species production. They are the site of important biochemical pathways, including the tricarboxylic acid cycle, parts of the ureagenesis cycle, or haem synthesis. Mitochondria are responsible for the majority of cellular ATP production through OXPHOS. Mitochondrial dysfunction has been associated with metabolic pathologies such as diabetes, obesity, hypertension, neurodegenerative diseases, cellular aging, and cancer. In this article, we describe the pathophysiological changes in, and mitochondrial role of, metabolic disorders (diabetes, obesity, and cardiovascular disease) and their correlation with oxidative stress. We highlight the genetic changes identified at the mtDNA level. Additionally, we selected several representative biomarkers involved in oxidative stress and summarize the progress of therapeutic strategies.